Differential role of the influenza A virus polymerase PA subunit for vRNA and cRNA promoter binding. - Maier, H; Kashiwagi, T; Hara, K; Brownlee, G (2008)
The RNA polymerase of influenza A virus is a heterotrimeric complex of PB1, PB2 and PA subunits that is required for transcription and replication of the viral genome. Here, we demonstrate a differential requirement of the PA subunit for binding to the vRNA and cRNA promoters--specifically, PA is more important for binding to the cRNA than the vRNA promoter. Furthermore, five point mutations were identified in the L163-I178 region of PA, which resulted in an inhibition of polymerase activity when provided with a cRNA compared to vRNA promoter. Cross-linking studies suggested that this inhibition was due to a reduction in promoter binding of the mutant polymerases to the cRNA promoter. We conclude that the L163-I178 region of PA is directly or indirectly involved in cRNA promoter binding and suggest a novel function for PA in modulating promoter binding.